STUDIES ON THE ELECTROPHORETIC PATTERN OF FISH MUSCLE MYOGENS - DEVADASAN, K; NAIR, M RAJENDRANATHAN (Fishery Technology, 2025)
Electrophoretic patterns of the muscle rnyogens of prawns and some common Indian food fishes of marine and fresh water origin were obtained on polyacrylamide gel. It was observed that the characteristic band pattern which was species specific and was not altered by storage of fish in ice, could be employed as a means of identification of fish species